A new Andean species of Aegidium Westwood (Coleoptera: Scarabaeidae: Orphninae: Aegidiini), with a key to the Colombian species of the genus. (2nd September 2021) - Gasca-Álvarez, Héctor Jaime; Deloya, Cuauhtémoc
ABSTRACT: A new Aegidium Westwood species from the East Andes Mountains in Colombia is described and illustrated. A key to the species of Aegidium from Colombia is provided in both English and Spanish. The check list of Aegidium especies of the New World is provided.